Nontuberculous Mycobacteria in Saudi Arabia and Gulf Countries: A Review - Hawra Al-Ghafli; Sahal Al-Hajoj (Canadian Respiratory Journal)
Nontuberculous Mycobacteria (NTM) are causing growing health problems worldwide. This is indicated by an increasing amount of scientific reports showing not only well-identified species reemerging but also emergence of new species. The emergence and reemergence of NTM are particularly worrying in developing countries due to scarce published data and improper identification. Here we aimed to examine the main epidemiological aspects and diagnostic challenges associated with NTM in countries of the Gulf Cooperation Council (GCC) and compare these findings to the international arena findings. Data revealed that countries of the GCC are largely dominated by rapidly growing mycobacteria species such as M. fortuitum (29%) and M. abscessus (17%) with high rate of definitive respiratory diseases. On the other hand, most of the developed countries are dominated by slowly growing mycobacteria such as MAC, M. kansasii, and M. gordonae. More efforts are needed, however, to gain insights into NTM issues in countries of the GCC.